DESIGN AND CONSTRUCTION OF A TEMPERATURE AND HUMIDITY AUTOMATION SYSTEM IN A MUSHROOM HOUSE USING RASPBERRY PI - Sudaryanto, Eko; Wahjudi, Dody; Daramawan, Isra' Nuur; Prasetyo, Rahardian Luthfi; Sukowati, Irawan Dharma; Setiawan, Dwi Agus (Program Studi Teknik Elektro Universitas Peradaban, 2025)
Air temperature and humidity factors can affect the growth and development of oyster mushroom plants. Ideally, oyster mushroom cultivation in highland areas has a low temperature, ranging from 22-28 ° C and humidity> 70%, if the cultivator wants to develop oyster mushroom cultivation has land / location in the lowlands which tends to have high temperatures, the mushrooms will die easily. In lowland locations the average temperature is 33-37 ° C, so there is a need for a tool that can control and monitor the humidity and temperature of the mushroom cultivation room, so that the cultivation room gets the ideal temperature. In this research, the author makes a monitoring system for air temperature and humidity using a DHT-11 sensor in Internet of Things-based oyster mushroom cultivation in an oyster mushroom cultivation house, if the temperature in the room is detected> 28 ° C, the Raspberry Pi microcontroller will give orders to the relay to turn on the fan and water pump. Fans and water pumps function to increase humidity and reduce temperature. This tool can certainly make it easier for us to monitor and control the temperature in the room, so that the temperature in the room can be maintained, so that oyster mushrooms can grow well and have good quality too.